2011
DOI: 10.1007/s10555-011-9284-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial deprivation, inflammation and cancer

Abstract: Dysregulated immune function is involved in the pathogenesis of many common human diseases. Living in urban, microbe-poor environment may have a profound influence on the immune function and eventually also on carcinogenesis. Unfortunately, few studies have thus far addressed the role of exposure to the environmental microbiota on the risk of cancer. Which mechanisms are broken in individuals prone to develop chronic inflammation in response to exposure that does not cause harm in others? Recent work in immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 120 publications
0
28
0
Order By: Relevance
“…The development and maintenance of epithelial-cell integrity, tolerance, and tissue repair requires the interaction with microbes and immune cells via their specific receptors. When these microbial stimuli are absent, it cannot adequately induce the immunoregulatory circuits including regulatory dendritic cells, regulatory T (Treg) cells and regulatory cytokines such as IL-10, transforming growth factor-β (TGF-β) 46. Interestingly, it has also been shown that an inflammatory milieu enhances the conversion of Treg cells to inflammatory Th17 cells and enriches the bacteria that tolerate to the inflammatory mediators in microbiota, thereby creating a self-perpetuating system.…”
Section: Introductionmentioning
confidence: 99%
“…The development and maintenance of epithelial-cell integrity, tolerance, and tissue repair requires the interaction with microbes and immune cells via their specific receptors. When these microbial stimuli are absent, it cannot adequately induce the immunoregulatory circuits including regulatory dendritic cells, regulatory T (Treg) cells and regulatory cytokines such as IL-10, transforming growth factor-β (TGF-β) 46. Interestingly, it has also been shown that an inflammatory milieu enhances the conversion of Treg cells to inflammatory Th17 cells and enriches the bacteria that tolerate to the inflammatory mediators in microbiota, thereby creating a self-perpetuating system.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation or infection could contribute to the development or activation of malignant disease. [18,19] PID might constitute a marker for gynecological cancers that could enable early treatment and improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dvorak actually described the tumor as an unhealed wound that produces a continuous source of inflammatory mediators (Dvorak, 1986). Inflammation is a component present during all steps of tumor development and in all types of tumors (Sansone & Bromberg, 2011;Spaeth et al, 2008;von Hertzen et al, 2011;Wallace et al, 2010). The migration of MSCs to tumors is well documented (Loebinger et al, 2009a(Loebinger et al, , 2009bNakamizo et al, 2005;Studeny et al, 2002Studeny et al, , 2004Xin et al, 2007).…”
Section: Msc Migration To Cancer Tissuementioning
confidence: 99%